The application of Information-Motivation-Behavioral Skills model-based whole-course nutritional management in elderly patients with esophageal cancer (基于信息-动机-行为技巧模型的全程化营养管理在老年食管癌患者中的应用研究) - TANG Ping (汤平); SUN Yun (孙云); WANG Lan (王兰) (中西医结合护理)
Objective To explore the effect of whole-process nutrition management based on Information-Motivation-Behavioral Skills (IMB)model in elderly patients with esophageal cancer. Methods Elderly patients with esophageal cancer surgery admitted to the Thoracic Surgery Department of hospital from July 2022 to January 2023 were selected as the study objects. According to the exclusion standard, patients from July 1, 2022 to September 30, 2022 were selected as the control group, with 37 participants. Patients from October 1, 2022 to January 31, 2023 were selected as the experimental group, with 38 participants. The control group received routine nutrition nursing management, while the experimental group took the whole process nutrition management based on IMB model on the basis of the control group. The postoperative recovery index, nutritional status, degree of fatigue, psychological status and nursing service satisfaction were compared between the two groups. Results After intervention, the nutrition monitoring indexes (albumin, hemoglobin, retinol binding protein and BMI) in the experimental group were higher than those in the control group 7 days after operation and 1 month after discharge form hospital, with significant difference (P＜0. 05). There were significant differences in scores of Borg Rating of Perceived Exertion Scale(Borg RPE) between the experimental group and the control group (P＜0. 05). The patient generated-subjective global assessment (PG-SGA) score of the experimental group before discharge and 1 month after operation was lower than that of the control group, and the difference was statistically significant (P＜0. 05). The scores of Hospital Anxiety and Depression Scale (HADS) indexes in the experimental group were significantly lower than those in the control group before discharge and 1 month after discharge from hospital, with significant difference (P＜0. 05). There was no significant difference in the score of service attitude between the experimental group and the control group (P＞0. 05), but the scores of other items in the experimental group were higher than those in the control group, and the difference was statistically significant (P＜0. 05). Conclusion The whole-process nutrition management based on IMB model can effectively improve the nutritional status of elderly patients undergoing esophageal cancer surgery and reduce their postoperative tiredness. It is also helpful to reduce the negative emotions of anxiety and depression and improve patients' satisfaction with nursing services. (目的 探讨基于信息-动机-行为技巧(IMB)模型的全程化营养管理在老年食管癌患者中应用效果。方法 选取2022年7月—2023年1月医院胸外科收治的老年食管癌手术患者为研究对象, 根据纳入和排除标准将2022年7月1日—9月30日收治的患者设为对照组(n=37), 将2022年10月1日—2023年1月31日收治患者设为对试验组(n=38)。对照组实施常规营养护理, 试验组在对照组基础上采取基于IMB模型的全程化营养管理。比较两组患者术后恢复指标、营养状况、疲乏程度、心理状况及护理服务满意度。结果 试验组术后7 d及出院后1个月营养监测指标中白蛋白、血红蛋白、视黄醇结合蛋白及体质指数(BMI)均优于对照组, 差异有统计学意义(P＜0. 05); 试验组Borg主观用力程度分级量表(Borg RPE)评分与对照组比较, 差异有统计学意义(P＜0. 05)。试验组出院前及术后1个月主观整体评估(PG-SGA)评分低于对照组, 差异有统计学意义(P＜0. 05)。出院前及出院1个月, 试验组医院焦虑抑郁量表(HADS)各项指数评分均较对照组显著降低, 差异有统计学意义(P＜0. 05)。试验组护士服务态度评分与对照组比较, 差异无统计学意义(P＞0. 05); 其他各项目试验组评分均高于照组, 差异有统计学意义(P＜0. 05)。结论 基于IMB模型的全程化营养管理, 可有效改善老年食管癌手术患者营养状况, 降低患者术后疲劳程度, 有利于减轻患者焦虑、抑郁负面情绪, 提高患者对护理服务的满意度。)